Changes in the soil pH, EC, available P, DOC and inorganic N after land use change from rice paddy in northeast Japan - Patria Novita Kusumawardani; Weiguo Cheng; Benito Heru Purwanto; Sri Nuryani Hidayah Utami (Center for Journal Management and Publication, 2017)
The objective of this study was to determine the changes in the basic soil chemical properties including pH, electrical conductivity (EC), available phosphorus (P), dissolved organic carbon (DOC) and inorganic Nitrogen (NH4+ -N and NO3- -N) after approximately 15-40 years land use change from rice paddy field to orchard, wetland and upland in northeast Japan. Five land use change fields were investigated, including, forest, rice paddy, orchard, wetland and upland near Kumagai shrine, Shonai-machi, Yamagata, Japan. Soil samples were collected from surface layer (0-15 cm) and subsurface layer (15-30 cm) in October 2015. Soil chemical properties of pH, EC, available P, DOC and inorganic N (NH4+ -N and NO3- -N) were analyzed on air-dried samples. The pH increased significantly in the upland after 15 years conversion from rice paddy in both layers, with other land use changes only increasing pH in subsurface layer. EC significantly decreased in the surface layer of orchard and upland fields and in subsurface layers of all the converted fields. Available P significantly decreased in the converted fields, except in the upland subsurface layer. DOC amounts were not significantly different after land use changes from paddy fields. The NH4+ -N decreased significantly only in the surface layer of upland, while NO3- -N increased significantly only in the surface layer of wetland. Significant changes in soil properties were observed after 15 years conversion to upland and 40 years conversion to orchard and wetland from former rice paddy field in this study.